Screening, isolation and characterisation of antimicrobial and antioxidant compounds from olea europaea subspecies africana leaves - Mamabolo, Kholofelo Sarah (My University, 2018)
Medicinal plants have been used as a key source for medication and they remain to provide new therapeutic remedies to date. Extracts of Olea europaea subspecies africana leaves are used extensively in South Africa to treat various diseases traditionally. The diseases have been noted to be associated with free radicals, bacterial infections, and inflammation. However, there is little information about the antioxidant, antibacterial, and anti-inflammatory activities of the leaves of this plant in literature and the cytotoxicity of the leaf extracts is still a concern. The information about the Isolated compounds is also minimal hence this study was aimed at filling in those gaps in relation to the traditional use of the leaves in southern Africa and subsequently isolating and identifying the active compounds using bioassay-guided fractionation. Preliminary screening of the crude extracts for antioxidant, antibacterial and antiinflammatory activities indicated that the extracts possessed all biological activities. The presence of major phytochemicals in the crude extracts was determined through the use of standard chemical methods and TLC analysis. The colorimetric methods (Folin-Ciocalteau and Aluminum chloride) were used for quantification purposes. TLC-DPPH assay was used to screen antioxidant activities of the crude extracts. The observed activity was quantified using the spectrophotometric method of DPPH and reducing power. The antibacterial properties of the leaf extracts were determined by direct bioautography and the serial broth microdilution assay using E. coli, P. aeruginosa, E. faecalis and S. aureus as test bacteria. Screening of the acetone crude extract for anti-inflammatory activities was done using the LPSstimulated RAW 264.7, cells where the inhibition of ROS generation was studied. MTT assay was used to determine the cytotoxicity effects of the leaves. Isolation of bioactive compounds started with serial exhaustive extraction, followed by column chromatography packed with silica gel. NMR analysis was conducted to identify the isolated compound. The results revealed the presence of tannins, terpenoids, steroids and flavonoids with the total phenolic (99.67 ± 2.52 mg of GAE/g) and tannin content (114.33 ± 9.02 mg of GAE/g) found in high amounts. All crude extracts exhibited antioxidant activities and the antioxidant activity quantified via the DPPH assay demonstrated to xxi have EC50 value of 1.05 ± 0.0071 mg/mL. The reducing capacity was found to be dose-dependent and great significance was seen at concentration 0.5 mg/mL to 1 mg/mL that was about 2/3 of that of L-ascorbic acid (standard) at a similar concentration. Screening of the crude extracts for antibacterial activity revealed that all crude extracts except n-hexane and water extracts, inhibited the growth of the tested bacteria on the previously developed TLC plates. The activity was seen as clear zones on the bioautograms. Serial broth microdilution assay indicated that dichloromethane, acetone and ethanol had average MIC values of 0.30, 0.32 and 0.35 mg/mL against all tested bacteria, respectively. Good anti-inflammatory activity of the crude extract was demonstrated at the highest concentration of 0.90 mg/mL. MTT assay indicated that the crude extract had no adverse cytotoxic effects. This was demonstrated by the LC50 values greater than 20 µg/mL and considered non-cytotoxic according to the National Cancer Institute (NCI). Isolation following the bioassay-guided-fractionation resulted in the selection of acetone extract to isolate the bioactive compounds from as it demonstrated good antioxidant and antibacterial activities. Fractionation of the compound by column chromatography yielded three combinations (pools) of fractions and of the three from which only pool 1 was considered for further fractionation. NMR spectra information identified the isolated compound as a mixture of ursolic acid (minor) and oleanolic acid (major). This compound had antibacterial and anti-inflammatory activities and no cytotoxic effects. The leaves of Olea europaea subspecies africana have been proven to possess antioxidant, antibacterial and anti-inflammatory properties. Evaluation of the biological activities of the crude extracts was to validate the use of the leaves traditionally to treat free radical and bacterial-related diseases and potential drug that are safe and has less side effects may be produced from the leaves.
Thesis ( |b(MSc. (Biochemistry)) -- University of Limpopo, 2017
Keywords: Medicianal plants; Olea europaea subspecies; Olea africana; Medicinal plants